Radio observations of the tidal disruption event AT2020opy: a luminous non-relativistic outflow encountering a dense circumnuclear medium. Issue 1 (31st October 2022) - Goodwin, A J; Miller-Jones, J C A; van Velzen, S; Bietenholz, M; Greenland, J; Cenko, B; Gezari, S; Horesh, A; Sivakoff, G R; Yan, L; Yu, W; Zhang, X
ABSTRACT: Tidal disruption events (TDEs) occur when a star passes too close to a supermassive black hole and is destroyed by tidal gravitational forces. Radio observations of TDEs trace synchrotron emission from outflowing material that may be ejected from the inner regions of the accretion flow around the supermassive black hole or by the tidal debris stream. Radio detections of TDEs are rare, but provide crucial information about the launching of jets and outflows from supermassive black holes and the circumnuclear environment in galaxies. Here, we present the radio detection of the TDE AT2020opy, including three epochs of radio observations taken with the Karl G. Jansky Very Large Array, MeerKAT, and upgraded Giant Metrewave Radio telescope. AT2020opy is the most distant thermal TDE with radio emission reported to date, and from modelling the evolving synchrotron spectra we deduce that the host galaxy has a more dense circumnuclear medium than other thermal TDEs detected in the radio band. Based on an equipartition analysis of the synchrotron spectral properties of the event, we conclude that the radio-emitting outflow was likely launched approximately at the time of, or just after, the initial optical flare. We find no evidence for relativistic motion of the outflow. The high luminosity of this event supports that a dense circumnuclear medium of the host galaxy produces brighter radio emission that rises to a peak more quickly than in galaxies with lower central densities.